Revitalisasi Kitab Kuning dalam Kurikulum Pesantren Melalui Literasi Media dan Informasi di Era Globalisasi - Yunita Sari; Siti Nuraini; Zubaidah Zubaidah; Suraiya Suraiya (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the revitalization of kitab kuning (classical Islamic texts) education in the era of globalization by emphasizing the integration of media and information literacy into the pesantren curriculum. As a legacy of classical Islamic scholarship, kitab kuning plays a central role in shaping character, strengthening Islamic understanding, and developing students’ critical reasoning. However, amidst the rapid growth of digital media, the teaching of kitab kuning faces serious challenges in terms of relevance and appeal. Using a qualitative approach through observation, in-depth interviews with pesantren leaders, teachers, and curriculum staff, as well as documentation of social media content at Pesantren Babussalam in Aceh Singkil, this study found that the strategic use of platforms such as TikTok and Instagram by teachers and students can offer a more contextual and engaging learning method that aligns with the learning styles of the digital generation. This technological integration not only enhances comprehension of classical texts but also equips students with digital literacy, 21st-century skills, and critical awareness in using media responsibly. Therefore, media literacy serves as a strategic instrument to preserve the relevance of kitab kuning while ensuring that pesantren remain adaptive to modern changes without losing their traditional roots.